Penerapan Terhadap Kepatuhan Konvensi Ballast Water Management Dari Awak Kapal Niaga Di Indonesia - Hugi Cerlyawati; Apriyanto Budhi Wibowo (International Forum of Researchers and Lecturers, 2023)
The International Maritime Organization (IMO) through the Environmental Protection Committee (MEPC/Marine Environment Protection Committee) since 2004 has established the international Convention on the Control and Management of Ship's Ballast Water and Sediments (BWM 2004), which seeks to protect marine waters from the impact of water discharge. commercial ship ballast The aim of this research is to determine the extent of implementation of the 2004 BWM Convention in Indonesia through questionnaires and interviews given to seafarer respondents in Indonesia. The compliance of commercial ship crews with PTES shows that the ship crews have not implemented the Ballast Water Management Convention, namely exchanging ship ballast water at sea according to standard D 1. The results of a questionnaire conducted on Indonesian merchant ship crews consisting of student crew members and student officers show that water exchange Ballast in the middle of the sea by merchant ships is only worth 14.5%. Commercial ships that have documents related to Ballast Water Management are also obtained below the 24% figure. PTES managers should manage ballast water at ports as the cheapest and most efficient solution compared to managing ballast water by commercial ships.